Self-Consistent Sources and Conservation Laws for a Super Broer-Kaup-Kupershmidt Equation Hierarchy. (18th June 2013) - Wei, Hanyu; Xia, Tiecheng
Abstract : Based on the matrix Lie superalgebras and supertrace identity, the integrable super Broer-Kaup-Kupershmidt hierarchy with self-consistent sources is established. Furthermore, we establish the infinitely many conservation laws for the integrable super Broer-Kaup-Kupershmidt hierarchy. In the process of computation especially, Fermi variables also play an important role in super integrable systems.